Feature selection for machine fault diagnosis using clustering of non-negation matrix factorization. (December 2016) - Liang, Lin; Liu, Fei; Li, Maolin; He, Kangkang; Xu, Guanghua
Abstract: Feature selection has been attracting more attentions in recent years for its advantages in improving the fault diagnosis efficiency and reducing the cost of feature acquisition. In this paper, we regard the feature selection as a clustering process with data decomposition technique and propose a novel feature selection method based on the non-negation matrix factorization (NMF). Alternating Least Squares (ALS) algorithm with sparsity control and decorrelation constrains is adopted to factorize original feature space into two low-rank matrixes (projection vectors and feature spaces). Considering the clustering distribution of the projection space, the optimal feature vectors are calculated by the means of the best updating rule parameters. Besides, the inverse of feature vectors is furtherly utilized in the seeking feature subset, which ensures high classifying performance. Experiments are performed by using two standard data sets and the fault diagnosis of roller bearing case. The results are compared with those obtained by applying the whole feature set and standard feature selection algorithms. The outcomes of comparative analysis have confirmed the effectiveness of the proposed approach.